Aggravation of ischemic brain injury by prion protein deficiency: Role of ERK-1/-2 and STAT-1 - Annett Spudich; Rico Frigg; Ertugrul Kilic; Ülkan Kilic; Bruno Oesch; Alex Raeber; Claudio L. Bassetti; Dirk M. Hermann (Neurobiology of Disease, 2005)
The cellular isoform of prion protein, PrPc, may confer neuroprotection in the brain, according to recent studies. To elucidate the role of PrPc in stroke pathology, we subjected PrPc-knockout (Prnp0/0), wild-type and PrPc-transgenic (tga20) mice to 30 min of intraluminal middle cerebral artery occlusion, followed by 3, 24 or 72 h reperfusion, and examined how PrPc levels influence brain injury and cell signaling. In immunohistochemical experiments and Western blots, we show that PrPc expression is absent in the brains of Prnp0/0 mice, detectable in wild-type controls and ∼4.0-fold elevated in tga20 mice. We provide evidence that PrPc deficiency increases infarct size by ∼200%, while transgenic PrPc restores tissue viability, albeit not above levels in wild-type animals. To elucidate the mechanisms underlying Prnp0/0-induced injury, we performed Western blots, which revealed increased activities of ERK-1/-2, STAT-1 and caspase-3 in ischemic brains of Prnp0/0 mice. Our data suggest a role of cytosolic signaling pathways in Prnp0/0-induced cell death.